PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PUSKESMAS MEKARSARI KECAMATAN RANGKASBITUNG - Zakiyya Tunnufus; Iqbal Maulana (The Asia Pacific Journal Of Management Studies, 2022)
Mekarsari Puskesmas, Rangkasbitung District, is one of the technical health offices responsible for health development in its working area, where it works. In improving health efforts optimally, the Puskesmas must have good management, therefore every leader must be able to retain employees to feel comfortable while working. The way to maintain it between them is with a leadership style and compensation. This study aims, (1) To obtain empirical data that leadership style affects employee performance (2) To obtain empirical data that compensation affects employee performance (3) To obtain empirical data that leadership style and compensation affect employee performance at Mekarsari Health Center Rangkasbitung District. The research method used is the associative quantitative method. The sampling technique used was saturated sampling. Saturated sampling is a sampling technique when all members of the population are used as samples. Because the population at the Mekarsari Health Center is 40 employees, the sample used is also 40 employees. Data collection techniques used were observation, literature study, questionnaires and documentation. The data analysis techniques used were normality test, heteroscedasticity test, autocorrelation test, multicolonierity test, multiple linear regression test, correlation coefficient test, determination coefficient test, t test and f test with the help of Statistical Package for The Social Science (SPSS) software Version 20.The results showed that partially leadership style has a positive effect on performance, and partially compensation also has a positive effect on performance. Meanwhile, simultaneously the two variables, namely leadership style and compensation, have a positive effect on performance, with the dominant variable affecting performance is compensation. The contribution of leadership style variables and compensation to performance was 72.4% and the rest was contributions from other variables not examined.